Development of Android-Based Algebra Educational Games: Student Responses and Learning Outcomes of Vocational Students - Aldo Setyoko; Firman Jaya; Rahmat Shofan Razaqi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Low learning motivation and mathematics achievement, particularly in basic algebra, remain common challenges in vocational high schools. This study aimed to develop an Android-based algebra educational game with a drag-and-drop mechanism and to identify students’ responses and changes in learning outcomes after using the game. The product was developed using Kodular (block-based programming). The game contains 10 basic algebra questions (e.g., operations on like terms) with a scoring system of 10 points for correct answers and 0 points for incorrect answers, accompanied by immediate feedback (notifications and text-to-speech). Prior to the trial, the product was validated by a content expert and a media expert using a 1-4 validation sheet to ensure the appropriateness of content, interface, and functionality; the test and questionnaire instruments were also reviewed for content validity through expert judgment. A limited trial was conducted with five Grade X students at SMKN 2 Situbondo using a one-group pretest–posttest design. The results show that the average score increased from 70 (pretest) to 76 (posttest), although gains varied across students. Student responses tended to be positive, especially regarding learning interest, drag-and-drop interaction, and confidence in solving algebra problems. These findings indicate that the Android-based educational game has the potential to serve as an engaging algebra practice medium to support classroom learning; however, further testing with a larger number of participants is needed to strengthen the generalizability of the results.